Co-pyrolysis of waste tyre and pine bark: Study of reaction kinetics and mechanisms. (January 2023) - Al-Balushi, Fahima A.; Burra, Kiran G.; Chai, Yue; Wang, Meihong
Abstract: Thermal processing of waste tyre and biomass through pyrolysis and gasification provides a promising pathway to address issues raised by anthropogenic activities including energy security, waste management and environmental sustainability. The study of the kinetics underlying the decomposition of the waste tyre and biomass blend through pyrolysis is an essential step to understand their further reactions in the reforming/cracking stage and to optimize their use. Kinetics analysis of the thermal decomposition of the waste tyre and pine bark with mass blend ratios of 1:0, 3:1, 1:1, 1:3 and 0:1 was investigated using thermogravimetric analysis. Results indicated that the change in heating rates from 10 to 40 K/min with an increment of 10 K/min caused a shift in differential thermogravimetry curves of all the samples to a higher temperature. To evaluate the possible interaction between waste tyre and pine bark in the blended samples, the difference in the weight loss ( Δw ) was calculated. Occurrence of positive synergetic interaction in terms of increased weight loss between waste tyre and pine bark at different blend ratios varied with the variation in heating rate. Activation energy and pre-exponential factor for different blend ratios were calculated using model fitting method (i.e. Coats-Redfern) and iso-conversional methods (i.e. FWO, KAS and Friedman) as well as combined kinetic analysis. Based on iso-conversional methods and combined kinetic analysis, the single waste tyre has higher activation energy than the single pine bark sample. However, waste tyre and pine bark blend samples with mass ratios of 3:1, 1:1 and 1:3 showed lower activation energy than waste tyre, signifying the benefits of using pine bark in blend samples. The maximum synergetic interaction in terms of lowest activation energy was reported with the use of the waste tyre and pine bark with a mass blend ratio of 3:1. The reaction mechanisms of WT1PB0, WT3PB1, WT1PB1, WT1PB3 and WT0PB1 were evaluated using the Sestak Berggren model and as follows; α − 1.866 ( 1 − α ) 1.000 [ − ln ( 1 − α ) ] − 2.276, α − 1.171 ( 1 − α ) 1.000 [ − ln ( 1 − α ) ] − 3.007, α 1.765 ( 1 − α ) 1.000 [ − ln ( 1 − α ) ] − 5.381, α − 2.324 ( 1 − α ) 2.913 [ − ln ( 1 − α ) ] − 1.272 and α − 7.735 ( 1 − α ) 5.658 [ − ln ( 1 − α ) ] 5.594, respectively. The results of the current study will contribute to the knowledge of expanding waste disposal options and provide essential information for the development of an energy sustainable system. Graphical abstract: Image 1 Highlights: Thermal decomposition of waste tyre, pine bark and their blends were studied. Three different methods were used for kinetic analysis of the co-pyrolysis process. Use of different heating rate showed different synergetic interaction as weight loss. Co-pyrolysis of 25 wt% pine bark with waste tyre led to minimum activation energy. Reaction mechanism of waste tyre and pine bark blends resemble high order reaction.